2004
DOI: 10.1111/j.1462-8902.2004.00329.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation and glycaemic control in type 2 diabetic patients

Abstract: Glycaemic control and diastolic blood pressure deteriorated in type 2 diabetic patients after quitting smoking. Type 2 diabetic patients who want to stop smoking need a caution to prevent deterioration of glycaemic control and blood pressure after quitting smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…In addition, Solberg et al [13] observed that the subjects with DM who smoke are less active in the care of their DM and are less interested in stopping smoking than smokers without DM. Some authors argue that subjects with DM who smoke are resistant to the idea of giving up smoking because of the fear that they will either gain weight or develop a related lack of appetite control and, later, a worsening of the metabolic control because tobacco helps them to control their weight [6,19,20]. Other authors comment that these patients, unlike other groups, feel that they are already so restricted by the need to maintain appropriate metabolic levels that they are unwilling to relinquish their smoking habit as well and do not see themselves as vulnerable or at risk of death [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Solberg et al [13] observed that the subjects with DM who smoke are less active in the care of their DM and are less interested in stopping smoking than smokers without DM. Some authors argue that subjects with DM who smoke are resistant to the idea of giving up smoking because of the fear that they will either gain weight or develop a related lack of appetite control and, later, a worsening of the metabolic control because tobacco helps them to control their weight [6,19,20]. Other authors comment that these patients, unlike other groups, feel that they are already so restricted by the need to maintain appropriate metabolic levels that they are unwilling to relinquish their smoking habit as well and do not see themselves as vulnerable or at risk of death [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…The datasheets for most recommended first-line smoking cessation medications31 caution against their use in diabetes 832 Moreover, studies report that smoking cessation may worsen metabolic profile and glycaemic control33 34 and lead to weight gain 35. We have identified four trials not included in the narrative review, two predating the narrative review 17…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is associated with insulin resistance [17], dyslipidaemia [18] and an increased propensity for type 2 diabetes [19, 20] through a body mass index-independent mechanism [21]. Contrary to what one might expect, stopping smoking does not reduce these metabolic abnormalities but, by mechanisms not well understood, is often accompanied by increased weight and a further increase in the risk of diabetes [22, 23]. …”
Section: Schizophrenia As An Independent Risk Factor For Metabolic Symentioning
confidence: 99%